Ergänzungen zum kartwelischen Wortschatz - Fähnrich , Heinz (Georgica, 2017)
The paper identifies certain lexemes of the Kartvelian languages that have not been included in recently published etymological dictionaries. Some of the material has been known for a long time but, for various reasons, has not been reflected in the dictionaries, while others represent new comparisons. This material can be reconstructed at either the Proto-Georgian-Zan or the Proto-Kartvelian chronological parent-language levels. Certain well-known materials are compared with each other differently in the present paper.